2016
DOI: 10.1016/j.gdata.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of microbial community of an Amazonian geothermal spring in Peru

Abstract: Aguas Calientes (AC) is an isolated geothermal spring located deep into the Amazon rainforest (7°21′12″ S, 75°00′54″ W) of Peru. This geothermal spring is slightly acidic (pH 5.0–7.0) in nature, with temperatures varying from 45 to 90 °C and continually fed by plant litter, resulting in a relatively high degree of total organic content (TOC). Pooled water sample was analyzed at 16S rRNA V3–V4 hypervariable region by amplicon metagenome sequencing on Illumina HiSeq platform. A total of 2,976,534 paired ends rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…The sludge samples from Shangyu WWTP mainly consisted of Acidobacteria, Proteobacteria, Candidatus phylum SBR1093, Chloroflexi and Thermi . Thermi has been found in geothermal springs all over the world and is known to be involved in NH 4 + –N removal (Coman et al 2015 ; Liang et al 2016 ; Panda et al 2016 ; Paul et al 2016 ). Due to the fact that industrial wastewater is usually discharged with an amount of heat, the influent temperature could hit 40 °C in summer.…”
Section: Resultsmentioning
confidence: 99%
“…The sludge samples from Shangyu WWTP mainly consisted of Acidobacteria, Proteobacteria, Candidatus phylum SBR1093, Chloroflexi and Thermi . Thermi has been found in geothermal springs all over the world and is known to be involved in NH 4 + –N removal (Coman et al 2015 ; Liang et al 2016 ; Panda et al 2016 ; Paul et al 2016 ). Due to the fact that industrial wastewater is usually discharged with an amount of heat, the influent temperature could hit 40 °C in summer.…”
Section: Resultsmentioning
confidence: 99%
“…The most studied thermophilic environment in the world is Yellowstone National Park (YNP) (pH 2, 75 • C) [1,5], where pioneering studies opened the possibility of exploring the diversity of microorganisms in extreme environments, as well as the genes that encode enzymes with biotechnological applications [3,[6][7][8]. Recently, a growing interest in studying these ecosystems has emerged [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22], and these studies have focused on the sites of high temperatures and acidic or alkaline pH [15,16,19,[23][24][25], and have identified a high diversity of microorganisms [22,26]. Intermediate or circumneutral hot springs also exhibit a high diversity of microorganisms; biodiversity generally decreases with increasing temperature and decreasing pH [21].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been reported as a key factor in the prevalence of Proteobacteria. Dominance of this phylum has been found in geographically distant but moderate-temperature (29–65 °C) geothermal springs like Deulajhari and Tattapani in India 25 , 26 , Aguas Calientes in the Amazon rainforest of Perú 27 , Chiraleu, Ciocaia, and Mihai Bravu in Romania 28 or El Coquito in the Colombian Andes 29 . Moreover, Power et al 30 found that the phyla Proteobacteria and Aquificae dominated in 925 geothermal springs in New Zealand (65.2% total average relative abundance across all springs), especially in hot springs with temperatures below 50 °C where Proteobacteria were the most abundant phylum.…”
Section: Resultsmentioning
confidence: 99%